The Effect of Foreign Direct Investment (FDI), Investment Portfolio, Exchange Rate, and Inflation on Current Account Balance (CAB) With Corruption Perception Index (CPI) As A Moderation Variable For The Period 1995-2022 In ASEAN-6 - Wairooy, Fatimah Az-zahra; Endraswati, Hikmah (Business Management Analysis Journal (BMAJ), 2023)
This study re-examines the effect of Foreign Direct Investment (FDI), portfolio investment, exchange rates, and inflation on the Current Account Balance (CAB), with the Corruption Perception Index (CPI) as a moderating variable for the 1995–2022 period in ASEAN-6. Hypothesis testing using MRA and panel data regression. This study took secondary data from The World Bank and Transparency International (TI). It used 168 samples obtained from six ASEAN countries: Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam. The results showed that Foreign Direct Investment (FDI) had a significant negative effect on Current Account Balance (CAB), portfolio investment had a significant positive effect on Current Account Balance (CAB), and exchange rates and inflation had no effect on Current Account Balance (CAB). In addition, the moderating variable used, namely the Corruption Perception Index (CPI), is proven to be able to moderate the four independent variables with a significant negative effect. This research is limited to ASEAN-6 countries and only uses CPI as a moderating variable. Suggestions for further research should be replicated outside ASEAN-6 and consider other variables.